Factors contributing to mortality in neonates with congenital diaphragmatic hernia and eventration - Raghunath Bangalore Vasudev; Nitin Kumar; Bahubali Deepak Gadgade; Veerabhadra Radhakrishna; Mamatha Basavaraju; Alladi Anand (Wolters Kluwer Medknow Publications, 2023)
Introduction: Despite all the advances, the mortality rate of congenital diaphragmatic hernia (CDH) ranges from 30% to 60% for isolated CDH and as high as 89% when they are associated with additional structural or chromosomal anomalies. Hence, a study was conducted to evaluate the factors contributing to the mortality of neonates treated for CDH or the eventration of diaphragm. Materials and Methods: A retrospective study was conducted in the department of paediatric surgery at a tertiary centre. The neonates admitted with a diagnosis of CDH or eventration requiring surgery, between March 2013 and March 2021, were included in the study. Results: A total of 123 neonates were included in the study. The variables, earlier median age at presentation (1 [1-23] vs. 3 [1-28]; P < 0.001; Mann-Whitney U-test), preterm birth (10/79 vs. 0/44; P = 0.01; Fischer's exact test), inborn (68/79 vs. 27/44; P = 0.002; Chi-square test), weight ≤2 kg (18/79 vs. 1/44; P = 0.003; Chi-square test), central cyanosis at presentation (21/79 vs. 1/44; P < 0.001; Chi-square test), antenatal detection (47/79 vs. 14/44; P = 0.003; Chi-square test) and earlier mean age at surgery (3.66 ± 1.47 vs. 7.66 ± 6.88; P < 0.001; Independent sample t-test) were associated with increased mortality. On multinominal logistic regression analysis, the factors preterm (odd's Ratio [OR] =4.735; P = 0.03), weight ≤2 kg (OR = 5.081; P = 0.02), central cyanosis at presentation (OR = 6.969; P = 0.008) and antenatal detection (OR = 7.471; P = 0.006) were found to be independently associated with increased mortality in CDH/eventration. Conclusion: The factors: prematurity, weight <2 kg, cyanosis at presentation and antenatal diagnosis were independently associated with increased mortality in neonates with CDH/eventration requiring surgery.